An Air-Stable Heterobimetallic Si2M2 Tetrahedral Cluster - Dübek, Gizem; Hanusch, Franziska; Munz, Dominik; Inoue, Shigeyoshi (Angewandte Chemie International Edition, 2020)
Air- and moisture-stable heterobimetallic tetrahedral clusters [Cp(CO)2MSiR]2 (M=Mo or W; R=SitBu3) were isolated from the reaction of N-heterocyclic carbene (NHC) stabilized silyl(silylidene) metal complexes Cp(CO)2M=Si(SitBu3)NHC with a mild Lewis acid (BPh3). Alternatively, treatment of the NHC-stabilized silylidene complex Cp(CO)2W=Si(SitBu3)NHC with stronger Lewis acids such as AlCl3 or B(C6F5)3 resulted in the reversible coordination of the Lewis acid to one of the carbonyl ligands. Computational investigations revealed that the dimerization of the intermediate metal silylidyne (M≡Si) complex to a tetrahedral cluster instead of a planar four-membered ring is due to steric bulk.
CRIS-Team Scopus Importer:2020-03-06
Keywords: cluster compounds; silicon; silylidenes; silylidynes; tetrahedranes